Treatment planning of total marrow irradiation with intensity-modulated spot-scanning proton therapy - Zuro, Darren M.; Vidal, Gabriel; Cantrell, James Nathan; Chen, Yong; Han, Chunhui; Henson, Christina; Ahmad, Salahuddin; Hui, Susanta; Ali, Imad (Frontiers in Oncology, 2022)
Purpose: The goal of this study is to investigate treatment planning of total marrow irradiation (TMI) using intensity-modulated spot-scanning proton therapy (IMPT). The dosimetric parameters of the intensity-modulated proton plans were evaluated and compared with the corresponding TMI-plans generated with volumetric-modulated-arc-therapy (VMAT) using photon beams. Methods: Intensity-modulated proton plans for TMI were created using the Monte-Carlo dose-calculation algorithm in the Raystation11A treatment planning system with spot-scanning-proton-beams from the MEVION S250i Hyperscan system. Treatment plans were generated with four isocenters placed along the longitudinal direction each with a set of 5 beams for a total of 20 beams. VMAT TMI plans were generated with the Eclipse-V15 analytical anisotropic algorithm (AAA) using a Varian Trilogy machine. Three planning-target-volumes (PTV) for bones, ribs, and spleen were covered by 12 Gy. The dose conformality-index, D80, D50 and D10 for PTVs and organs at risk (OARs) for the IMPT-plans were quantified and compared with the corresponding VMAT plans. Results: The mean dose for most of the OARs was reduced substantially (5% and more) in the IMPT plans for TMI in comparison with VMAT plans, while maintaining comparable dose coverage for the PTVs. This dose reduction is due to the fast dose fall-off of the distal Bragg peak in the proton plans. The conformality index was found to be similar (0.78 vs 0.75) for the photon and proton plans. IMPT-plans provided superior superficial dose coverage for the skull and ribs in comparison with VMAT because of increased entrance dose deposition by the proton beams. Conclusion: Treatment plans for TMI generated with IMPT were superior to VMAT plans mainly due to large reduction in the OAR dose. Although the current IMPT-TMI technique is not clinically practical due to long overall treatment time, this study presents an enticing alternative to conventional TMI with photons by providing superior dose coverage of the targets, increased sparing of the OARs and enhanced radiobiological effects associated with proton therapy.